The Numerical Modeling of Microbial Reductive Dechlorination: Monod Kinetic Parameter Estimation and Uncertainty Analysis - Elsey, John. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Civil Engineering.; Advisor: Linda Abriola.; Committee: Natalie Cápiro, John Christ, Jonathan Lamontagne, and Eric Miller.; Keywords: Environmental engineering, and Statistics.